Critical Factors For The Effective Safety Management System Of Construction Project Sites In Perak - Azli, Shahrul Amin Saifol (Universiti Sains Malaysia, 2021)
Construction industry is one of the important sectors in the Malaysian economy that have their own contribution in terms of development but can be classified as one of the risky industries in the world. However, there have been significant reductions in the number and the rate of accident and fatality over the last 20 years or more. Nevertheless, according to the record, the construction industry remains as the one of the high-risk industries in Malaysia. The purpose of this study is to examine safety management system in the Malaysian construction industry, as well as to highlight the critical factor that influenced the effectiveness of safety management systems especially at construction sites. This industry has contributed significantly to the economic growth of the country. However, when construction safety management systems are not implemented systematically, accidents will happen, and this can affect this industry’s reputation and economy growth. The research focuses on construction projects in Perak, Malaysia. The data was collected by doing a questionnaire survey and a case study method. The priority important of each factor in safety management system is suggested from the interview session and the data is from the perspective of contractor team at the real construction project. Then, data analysis was performed by using the Analytical Hierarchy Process Pairwise comparison in Expert Choice software and the result produced the hierarchy of priority importance among all the critical factors. This research contributes to identifying the critical factors related to the effectiveness of safety management system at construction sites in Perak, Malaysia.